2020
DOI: 10.12659/msm.922753
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combined Hemodialysis and Hemoperfusion with Hemoperfusion Alone in 106 Patients with Diabetic Ketoacidosis and Acute Renal Failure: A Retrospective Study from a Single Center in China

Abstract: Background Acute kidney injury with acute renal failure is associated with severe diabetic ketoacidosis. This retrospective study was conducted at a single center in China and aimed to compare combined hemodialysis and hemoperfusion (hemodialysis+hemoperfusion) with hemoperfusion alone in 106 patients with diabetic ketoacidosis and acute renal failure. Material/Methods The 106 patients were divided into 2 groups according to different dialysis programs, with 53 cases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Further intra-group comparisons showed that the indices of the two groups were significantly higher before treatment than after treatment, indicating that hemodialysis combined with hemoperfusion can effectively improve the renal function of patients, reduce inflammatory reactions, and improve the toxin clearance effect, thus helping to reduce tissue damage and improve the treatment effect. The research of Wang et al 34 . shows that the combined treatment of hemodialysis and hemoperfusion can improve renal function, significantly reduce pruritus and anemia in patients with acute renal failure, and effectively reduce the incidence of adverse events, which is similar to our research.…”
Section: Discussionmentioning
confidence: 99%
“…Further intra-group comparisons showed that the indices of the two groups were significantly higher before treatment than after treatment, indicating that hemodialysis combined with hemoperfusion can effectively improve the renal function of patients, reduce inflammatory reactions, and improve the toxin clearance effect, thus helping to reduce tissue damage and improve the treatment effect. The research of Wang et al 34 . shows that the combined treatment of hemodialysis and hemoperfusion can improve renal function, significantly reduce pruritus and anemia in patients with acute renal failure, and effectively reduce the incidence of adverse events, which is similar to our research.…”
Section: Discussionmentioning
confidence: 99%
“…It ensures timely excretion of metabolites, such as urea nitrogen and creatinine, and allows to effectively maintain fluid balance and prevent electrolyte and acid-base disturbances. 4 However, studies have found that hemodialysis treatment is associated with cardiovascular instability and significant fluctuations in the levels of metabolites and electrolytes 5 With the recent developments in medical technology, CRRT has been gradually introduced as a treatment option for patients with AKI. CRRT is a continuous and long-term in vitro blood purification for 24 hours or nearly 24hours/day that has the advantages of being a highly safe and effective method.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, while original hemoperfusion techniques presented significant side effects and adverse reactions, highly biocompatible new sorbent materials, represent today a possibility for incremental application of adsorption in acute and chronic blood purification therapies [13][14][15][16][17][18][19]. In the last domain, initial reports of application of hemoperfusion combined with HD in chronic patients with pruritus and other middle molecule-related symptoms have provided encouraging results [20]. In a prospective randomized controlled trial on more than 400 chronic HD patients, Zhao et al [21] made an important observation supporting the use of hemoperfusion combined with HD (HP + HD).…”
mentioning
confidence: 99%